2018
DOI: 10.2131/jts.43.485
|View full text |Cite
|
Sign up to set email alerts
|

Polyhexamethylene guanidine phosphate induces IL-6 and TNF-α expression through JNK-dependent pathway in human lung epithelial cells

Abstract: Polyhexamethylene guanidine phosphate (PHMG) is an antimicrobial biocide that causes severe lung injury accompanied with inflammation and subsequent fibrosis. Cytokines mediate the inflammatory response, leading to fibrosis in injured tissues. PHMG is known to induce the expression of various cytokines in vitro and in vivo. In the present study, we investigated the involvement of three MAPK subfamilies (JNK, p38 MAPK, and ERK) in PHMG-induced cytokine expression in A549 human lung epithelial cells. Our in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Adding WP9QY (TNF-α inhibitor) and N-acetylcysteine (ROS antioxidant) partially inhibited the expression of IL-8 caused by PHMB. By the way, the JNK inhibitor SP600125 could also partially inhibit the PHMG-induced expression of IL-6 and TNF-α in A549 cells (21). However, addition of the NFκB inhibitor completely inhibited the expression of IL-8, suggesting that PHMB induces inflammation through the NFκB signaling pathway (18).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Adding WP9QY (TNF-α inhibitor) and N-acetylcysteine (ROS antioxidant) partially inhibited the expression of IL-8 caused by PHMB. By the way, the JNK inhibitor SP600125 could also partially inhibit the PHMG-induced expression of IL-6 and TNF-α in A549 cells (21). However, addition of the NFκB inhibitor completely inhibited the expression of IL-8, suggesting that PHMB induces inflammation through the NFκB signaling pathway (18).…”
Section: Discussionmentioning
confidence: 96%
“…Since the Korean humidifier lung injury incident, many studies have been performed to understand the mechanisms by which PHMG and its related guanidine disinfectants cause lung inflammation (10,(18)(19)(20)(21)(22) and pulmonary fibrosis (12,(22)(23)(24)(25)(26). One study showed that exposure of mouse macrophage RAW264.7 cells to PHMG decreased IκB protein expression, increased NFκB luciferase activity, and elevated the expression of inflammatory cytokines IL-1β, IL-6, and IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…Seen in the most types of human diabetic nephropathy, the activation of the JNK pathway can worsen symptoms and inhibiting the JNK pathway is a therapeutic target for diabetic nephropathy [34]. JNKs not only have a role in the synthesis of a variety of infammatory cytokines but also the expression of proinfammatory cytokines, such as TNF-α and IL-6, is linked to the continued activation of JNK1 [35,36]. Activated by multiple pathogens and other infammatory diseases, JNK is able to phosphorylate c-Jun, triggering a series of phosphorylation cascade events and regulating critical downstream efector molecules such as TNF-α, IL-6, IL-1, ICAM-1 to exert its biological impact [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…One in vivo study of PGH showed that exposure through intratracheal instillation in mice can increase cytokine and fibronectin levels [ 10 ]. In vivo studies of PHMG also showed that exposure through inhalation and intratracheal instillation in rats can induce the release of pro-inflammatory cytokines and cause fibronectin mRNA expression and histopathological changes in lung tissues [ 26 , 27 ]. In vitro studies of PHMG and CMIT/MIT suggested that their exposures can induce the release of proinflammatory cytokines in macrophages and alveolar epithelial cells in mice, respectively [ 8 , 28 ].…”
Section: Discussionmentioning
confidence: 99%